Fractal attractor based digital signature - Al-Saidi, Nadia M. G.; Md. Said, Mohamad Rushdan (IEEE, 2010)
Fractal theories are applied to enhance the efficiency and performance of cryptosystem due to their inherent complexity and mathematical framework. A new digital signature scheme based on Iterated Function System (IFS) is proposed, which can reduce computation cost and increase security of the system. The properties of the proposed system are discussed in detail.